Simple field-based surveys reveal climate-related anomalies in mountain grassland production. (September 2020) - Grigulis, Karl; Lavorel, Sandra
Highlights: Sward height is a reliable indicator of grassland peak biomass climate sensitivity. Growth season temperature is the primary driver of mountain grassland peak biomass. Different grassland types have differing sensitivities, allowing farmers' adaptation. Recent early summer temperature extremes reduced fodder production. Abstract: Sensitivity of grassland biomass production to climate is critical to impacts on multiple ecological processes and ecosystem services. Understanding its climate determinants is essential for climate change adaptation. This requires long-term monitoring, using robust methods that are appropriated by stakeholders. We tested the sensitivity of easily measured sward height to interannual climate variation in mountain grasslands. Using twelve consecutive years of measurements across 67 grassland plots representative of six land-use types associated with different landscape positions, we show that peak green biomass increased with mean summer months (June and July) maximum temperature. Different land-use types responded to specific combinations of climate parameters, but all except higher-elevation summer pastures were sensitive to summer months temperatures. We did not detect any effects of drought, with summer precipitation instead decreasing peak biomass of some grasslands due to cooling and cloudiness, also suggesting that soil water recharge from snowmelt was enough to sustain the first growth cycle. Summer pasture peak biomass decreased with number of frosts during the onset of growth in May. These result support the robustness and sensitivity of sward height as an indicator for climate response of peak fodder biomass. Differential responses across land-use types suggest some resource complementarity which can support tactical adaptation for farmers. During the three recent hottest summers (2015, 2017 and 2018) production was well below predicted values from actual temperatures, suggesting a potential regime shift when the vegetative growth period is shortened by temperature-driven acceleration in phenology and/or heat stress combined with high light intensity causing physiological damage. The baseline regime and the anomalies in hottest years need confirmation for longer time series and across a greater geographic extent. Further effects of drought and of an extended growing season are also likely for post-harvest or grazing regrowth.